Method for recovering and repairing waste lithium iron phosphate powder

Through high-temperature solid phase combined with redox technology and multiple grinding, drying and calcining steps, waste lithium iron phosphate was successfully repaired and recovered, solving the problems of high cost, high energy consumption and environmental pollution of the existing recycling methods, and preparing low-carbon battery-grade lithium iron phosphate with excellent performance.

CN119742485APending Publication Date: 2025-04-01JIANGXI GANFENG RECYCLING TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411920407.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing lithium battery positive electrode material recycling methods have problems such as high cost, high energy consumption and high environmental pollution.

Method used

Using a high-temperature solid phase combined with redox technology, waste lithium iron phosphate is roasted into powder under a protective atmosphere, and then mixed with iron source, lithium source, phosphorus source and alcohol. After grinding, drying and calcining, low-carbon lithium iron phosphate powder is formed. By mixing with the carbon source again, grinding, drying and calcining, low-carbon battery-grade lithium iron phosphate is finally prepared.

Benefits of technology

The lithium missing in waste lithium iron phosphate materials has been repaired, the content of carbon and impurity elements has been reduced, and the prepared lithium iron phosphate products have low carbon content, high 1C discharge specific capacity, meet battery-grade standards, and are simple in process, environmentally friendly and have low production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119742485A_ABST
    Figure CN119742485A_ABST
Patent Text Reader

Abstract

The invention provides a method for recycling and repairing waste lithium iron phosphate powder, and relates to the technical field of recycling of waste batteries. The repairing method comprises the following steps: roasting waste lithium iron phosphate in a protective atmosphere to obtain waste lithium iron phosphate powder; the method comprises the following steps: mixing waste lithium iron phosphate powder, an iron source, a lithium source and alcohol, and sequentially grinding and drying to obtain a low-carbon lithium iron phosphate precursor; calcining the low-carbon lithium iron phosphate precursor in a protective atmosphere to obtain low-carbon lithium iron phosphate powder; and mixing the low-carbon lithium iron phosphate powder, a carbon source and ethanol, and sequentially grinding, drying and calcining to obtain the low-carbon battery-grade lithium iron phosphate. According to the method, a high-temperature solid-phase combined oxidation-reduction process is adopted, lithium iron phosphate is synthesized by adding an iron source, a lithium source and a phosphorus source and using carbon in lithium iron phosphate powder as reduction carbon, lithium deficient in the waste lithium iron phosphate material can be supplemented, and the content of carbon and impurity elements in the material can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of waste battery recycling, and in particular to a method for recycling and repairing waste lithium iron phosphate powder. Background Art

[0002] As the demand for power batteries in the new energy market increases, lithium-ion batteries stand out from many types of power batteries due to their excellent comprehensive performance such as environmental protection, high energy density, light weight, no "memory effect" and long cycle life, and gradually become the mainstream power battery for new energy vehicles. The market structure of supply exceeding demand has led to excessive mining of lithium battery raw materials and a sharp rise in prices. Under the "dual carbon policy" and the scarcity of mineral resources, many companies have begun to work on the recycling of lithium battery resources.

[0003] There are three methods for recycling positive electrode materials of lithium batteries: wet recycling, pyrolysis and solid phase repair. Wet recycling is currently the most widely used process in domestic industrial applications. This method can recover valuable elements in positive electrode materials to a large extent, and the product recovery rate and purity are high, but the disadvantages are also obvious. It is necessary to add expensive reagents, and the consumption is huge. The whole process will produce a variety of hazardous waste residues and high-salt organic wastewater, which seriously threatens the ecological environment. The economic removal of organic matter under high-salt systems has also been a difficult problem in the field of wastewater treatment for a long time; pyrolysis recovery is mainly through high-temperature pyrolysis to obtain metal oxides. The recovery process is simple, but the recovery rate is low, the energy consumption is high, and certain waste pollution will be generated. Therefore, how to disclose a method for repairing waste lithium iron phosphate powder that is simple to operate, high in economic benefits, and environmentally friendly has become a problem that needs to be solved urgently by technicians in this field. Summary of the invention

[0004] The purpose of the present invention is to provide a method for recycling and repairing waste lithium iron phosphate powder, so as to solve the problems of high cost, high energy consumption and easy pollution to the environment in the existing methods for recycling lithium battery positive electrode materials.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for recovering and repairing waste lithium iron phosphate powder, comprising the following steps:

[0007] 1) calcining waste lithium iron phosphate under a protective atmosphere to obtain waste lithium iron phosphate powder;

[0008] 2) mixing waste lithium iron phosphate powder, an iron source, a lithium source, a phosphorus source and an alcohol, and grinding and drying them in sequence to obtain a low-carbon lithium iron phosphate precursor;

[0009] 3) calcining the low-carbon lithium iron phosphate precursor under a protective atmosphere to obtain low-carbon lithium iron phosphate powder;

[0010] 4) mixing low-carbon lithium iron phosphate powder, a carbon source and ethanol, grinding, drying and calcining in sequence to obtain low-carbon battery-grade lithium iron phosphate;

[0011] The waste lithium iron phosphate includes one or more of retired lithium iron phosphate positive electrode materials, unqualified slurry in the production process of lithium iron phosphate batteries, and unfilled defective products in the production process.

[0012] Preferably, the calcination temperature in step 1) is 400-600° C. and the calcination time is 0.1-2 h.

[0013] Preferably, the amount of the iron source added in step 2) is 10-60% of the mass of the waste lithium iron phosphate powder;

[0014] The molar ratio of Li, Fe and P elements in the lithium source, iron source and phosphorus source is 1.01-1.05:1:1.00-1.03;

[0015] The grinding speed is 500-1000 r / min, and the grinding time is 1-12 h.

[0016] Preferably, the iron source in step 2) is ferric phosphate and / or ferric oxalate;

[0017] The lithium source is one or more of lithium phosphate, lithium oxalate and lithium carbonate;

[0018] The phosphorus source is one or more of lithium phosphate, iron phosphate and phosphoric acid.

[0019] Preferably, the calcination in step 3) is firstly carried out at 300-500°C for 2-12 hours, and then at 600-800°C for 2-12 hours.

[0020] Preferably, the amount of the carbon source added in step 4) is 1-10% of the mass of the low-carbon lithium iron phosphate powder.

[0021] Preferably, the carbon source in step 4) is one or more of glucose, sucrose, starch, acetylene black and carbon nanotubes.

[0022] Preferably, the grinding speed in step 4) is 500-1000 r / min, and the grinding time is 1-12 h.

[0023] Preferably, the calcination temperature in step 4) is 500-700° C. and the calcination time is 1-4 hours.

[0024] The present invention has at least the following beneficial effects:

[0025] The raw materials of the present invention are unfilled defective products produced in a workshop, retired lithium iron phosphate positive electrode materials, and unqualified slurry in the production process of lithium iron phosphate batteries. A high-temperature solid-phase combined oxidation-reduction process is adopted, and the carbon in lithium iron phosphate powder is used as reducing carbon to synthesize lithium iron phosphate by adding an iron source, a lithium source, and a phosphorus source. On the one hand, the missing lithium in the waste lithium iron phosphate material can be supplemented, and on the other hand, the content of carbon and impurity elements is reduced. The lithium iron phosphate prepared by this process has a carbon content of 1.05%, a 1C discharge specific capacity of more than 140 mAh / g, and other impurity element indicators meet the industry standards for battery-grade lithium iron phosphate, and can be well applied in the small power and energy storage battery industries.

[0026] The present invention has the advantages of simple repair process, environmental friendliness, low production cost, excellent product performance, etc., and solves the problems of lack of lithium and high impurity content in waste lithium iron phosphate materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the XRD pattern of the low-carbon battery-grade lithium iron phosphate prepared in Example 1 of the present invention;

[0028] Figure 2 This is an electrochemical performance diagram of low-carbon battery-grade lithium iron phosphate prepared in Example 2 of the present invention;

[0029] Figure 3 a in the figure is a microscopic morphology of the lithium iron phosphate positive electrode sheet before repair in Example 3 of the present invention; Figure 3 b is a microscopic morphology of the low-carbon battery-grade lithium iron phosphate prepared in Example 3 of the present invention. DETAILED DESCRIPTION

[0030] The present invention provides a method for recovering and repairing waste lithium iron phosphate powder, comprising the following steps:

[0031] 1) calcining waste lithium iron phosphate under a protective atmosphere to obtain waste lithium iron phosphate powder;

[0032] 2) mixing waste lithium iron phosphate powder, an iron source, a lithium source, a phosphorus source and an alcohol, and grinding and drying them in sequence to obtain a low-carbon lithium iron phosphate precursor;

[0033] 3) calcining the low-carbon lithium iron phosphate precursor under a protective atmosphere to obtain low-carbon lithium iron phosphate powder;

[0034] 4) mixing low-carbon lithium iron phosphate powder, a carbon source and ethanol, grinding, drying and calcining in sequence to obtain low-carbon battery-grade lithium iron phosphate;

[0035] The waste lithium iron phosphate includes one or more of retired lithium iron phosphate positive electrode materials, unqualified slurry in the production process of lithium iron phosphate batteries, and unfilled defective products in the production process.

[0036] In the present invention, the waste lithium iron phosphate contains the following components: Li, Fe, P, Al, F, Ti and a current collector aluminum foil as a conductive material of the battery structure.

[0037] In the present invention, the calcination temperature in step 1) is 400-600°C, preferably 450-550°C, and more preferably 480-520°C; the time is 0.1-2h, preferably 0.5-1.75h, and more preferably 1-1.5h; in this process, the binder polyvinylidene fluoride (PVDF) in the waste lithium iron phosphate material decomposes at high temperature, a part of which decomposes into hydrogen fluoride and short-chain fluorinated hydrocarbons and enters the exhaust gas absorption system with the flue gas, and the other part chemically reacts with the impurities of the current collector aluminum foil in the waste lithium iron phosphate to exist in the form of aluminum fluoride. The high-temperature pyrolysis characteristics of the above PVDF realize the separation of the current collector aluminum foil and the active substance lithium iron phosphate. The carbon content of the separated lithium iron phosphate is generally above 3.5%, while the carbon content of the battery-grade lithium iron phosphate is generally within 1.5%. The high carbon content is partly due to the conductive carbon added during the battery manufacturing process, and the other part is due to the pyrolytic carbon generated by PVDF during the high-temperature pyrolysis process.

[0038] In the present invention, the protective atmosphere in step 1) can be selected from one or more of nitrogen, argon, helium or neon.

[0039] In the present invention, after the calcination in step 1) is completed, the step of washing and drying the waste lithium iron phosphate powder is also included, and the drying temperature is 80-120°C, preferably 85-115°C, more preferably 90-110°C, and more preferably 95-105°C; the drying time is 1-24h, preferably 4-20, more preferably 8-16h, and more preferably 10h.

[0040] In the present invention, the amount of the iron source added in step 2) is 10-60% of the mass of the waste lithium iron phosphate powder, preferably 20-50%, more preferably 30-40%, and more preferably 32-38%;

[0041] The molar ratio of Li, Fe and P elements in the lithium source, iron source and phosphorus source is 1.01-1.05:1:1.00-1.03, preferably 1.015-1.045:1:1.005-1.027, and more preferably 1.018-1.044:1:1.007-1.024.

[0042] In the present invention, the grinding speed is 500-1000 r / min, preferably 600-900 r / min, more preferably 700-800 r / min; the grinding time is 1-12 h, preferably 3-10 h, more preferably 5-8 h.

[0043] In the present invention, the grinding method in step 2) is preferably ball milling.

[0044] In the present invention, the iron source in step 2) is iron phosphate and / or iron oxalate.

[0045] In the present invention, the lithium source in step 2) is one or more of lithium phosphate, lithium oxalate and lithium carbonate.

[0046] In the present invention, the phosphorus source in step 2) is one or more of lithium phosphate, iron phosphate and phosphoric acid.

[0047] In the present invention, the drying method in step 2) is spray drying, and the inlet air temperature of the spray drying is 250-350°C, preferably 270-330°C, more preferably 290-310°C, and more preferably 300°C; the outlet air temperature is 90-110°C, preferably 95-105°C, more preferably 98-102°C, and more preferably 100°C; the atomization frequency is 40-50Hz, preferably 42-48Hz, more preferably 44-46Hz, and more preferably 45Hz.

[0048] In the present invention, the calcination in step 3) is first kept at 300-500°C for 2-12 hours, and then kept at 600-800°C for 2-12 hours, preferably first kept at 350-450°C for 4-10 hours, and then kept at 630-780°C for 4-10 hours, and more preferably first kept at 380-420°C for 6-8 hours, and then kept at 650-750°C for 6-8 hours.

[0049] In the present invention, the calcination atmosphere in step 3) is nitrogen or a rare gas atmosphere, specifically one or more of nitrogen, argon, helium or neon.

[0050] In the present invention, after the calcination in step 3) is completed, a washing and drying step is also included, and the drying temperature is 80-120°C, preferably 90-110°C, more preferably 95-105°C, and more preferably 98-100°C; the drying time is 1-24h, preferably 10-20h, more preferably 12-18h, and more preferably 15h.

[0051] In the present invention, the amount of the carbon source added in step 4) is 1-10% of the mass of the low-carbon lithium iron phosphate powder, preferably 2-8%, more preferably 4-6%, and more preferably 5%.

[0052] In the present invention, the carbon source in step 4) is one or more of glucose, sucrose, starch, acetylene black and carbon nanotubes.

[0053] In the present invention, the grinding speed in step 4) is 500-1000 r / min, preferably 600-900 r / min, more preferably 700-800 r / min; the grinding time is 1-12 h, preferably 3-10 h, more preferably 5-8 h.

[0054] In the present invention, the grinding method in step 4) is preferably ball milling.

[0055] In the present invention, in step 4), the drying method is spray drying, the inlet air temperature of the spray drying is 250-350°C, preferably 270-330°C, more preferably 290-310°C, and more preferably 300°C; the outlet air temperature is 90-110°C, preferably 95-105°C, more preferably 98-102°C, and more preferably 100°C; the atomization frequency is 40-50Hz, preferably 42-48Hz, more preferably 44-46Hz, and more preferably 45Hz.

[0056] In the present invention, the calcination temperature in step 4) is 500-700°C, preferably 530-680°C, more preferably 550-650°C, more preferably 580-620°C; the calcination time is 1-4h, preferably 1.5-3.5h, more preferably 2-3h.

[0057] In the present invention, the calcination atmosphere in step 4) is nitrogen or a rare gas atmosphere, specifically one or more of nitrogen, argon, helium or neon.

[0058] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0059] Example 1

[0060] Step 1: The disassembled lithium iron phosphate positive electrode sheet is calcined at 400°C for 30 minutes under an argon atmosphere, the calcined waste lithium carbonate powder is washed with water, and then dried at 95°C for 12 hours to obtain waste lithium iron phosphate powder;

[0061] Step 2: Add iron phosphate and lithium oxalate to the waste lithium iron phosphate powder obtained in step 1, and add iron phosphate to 30% of the mass of the waste lithium iron phosphate powder. Use lithium oxalate as the lithium source and iron phosphate as the phosphorus source. Control the molar ratio of Li:Fe:P in the added lithium source, iron source, and phosphorus source to be 1.01:1.00:1.00 and disperse them in anhydrous ethanol (the mass ratio of anhydrous ethanol to the waste lithium iron phosphate powder is 1:1). Place the dispersed slurry in a planetary ball mill at a speed of 600 rpm for 5 hours, and then use a spray dryer to spray dry the slurry after ball milling. The spray dryer has an air inlet temperature of 250°C, an air outlet temperature of 90°C, and an atomization frequency of 40 Hz to obtain a low-carbon lithium iron phosphate precursor;

[0062] Step 3: The low-carbon lithium iron phosphate precursor obtained in step 2 is first kept at 350° C. for 2 hours and then kept at 600° C. for 10 hours under an argon atmosphere, and then washed and dried to obtain low-carbon lithium iron phosphate powder;

[0063] Step 4: Disperse the low-carbon lithium iron phosphate powder and glucose obtained in step 3 in anhydrous ethanol to obtain a mixed slurry, the mass ratio of anhydrous ethanol to low-carbon lithium iron phosphate powder is 1:1, and the amount of glucose added is 5% of the mass of the low-carbon lithium iron phosphate powder. The mixed slurry is placed in a planetary ball mill for ball milling, the ball milling time is 10 hours, the ball milling speed is 500r / min, and then the ball-milled slurry is spray-dried using a spray dryer, the spray dryer has an air inlet temperature of 250°C, an air outlet temperature of 105°C, and an atomization frequency of 40Hz, to obtain a carbon-coated low-carbon lithium iron phosphate precursor;

[0064] Step 5: The carbon-coated low-carbon lithium iron phosphate precursor obtained in step 4 is calcined at 650° C. for 4 hours under an argon atmosphere to obtain low-carbon battery-grade lithium iron phosphate.

[0065] The material discharged from step 5 is conventionally crushed and packaged to obtain a battery-grade lithium iron phosphate product with a carbon content of 1.02% and a discharge specific capacity of 142 mAh / g at 1C.

[0066] Example 2

[0067] Step 1: The disassembled lithium iron phosphate positive electrode sheet is calcined in a nitrogen atmosphere at a temperature of 500° C. for 60 minutes, the calcined waste lithium carbonate powder is washed with water, and then dried at 95° C. for 12 hours to obtain waste lithium iron phosphate powder;

[0068] Step 2: Add ferric oxalate, lithium carbonate and phosphoric acid to the waste lithium iron phosphate powder obtained in step 1, wherein the ferric oxalate added is 35% of the mass of the waste lithium iron phosphate powder, lithium carbonate is used as the lithium source, phosphoric acid is used as the phosphorus source, and the molar ratio of Li:Fe:P in the added lithium source, iron source and phosphorus source is controlled to be 1.02:1.00:1.00 and dispersed in anhydrous ethanol (the mass ratio of anhydrous ethanol to the waste lithium iron phosphate powder is 1:1), and the dispersed slurry is placed in a planetary ball mill and ball-milled at a speed of 800 rpm for 6 hours, and then the ball-milled slurry is spray-dried by a spray dryer, the spray dryer has an air inlet temperature of 300°C, an air outlet temperature of 100°C, and an atomization frequency of 45Hz, to obtain a low-carbon lithium iron phosphate precursor;

[0069] Step 3: The low-carbon lithium iron phosphate precursor obtained in step 2 is first kept at 400° C. for 2 hours and then kept at 700° C. for 11 hours under a nitrogen atmosphere, and then washed and dried to obtain low-carbon lithium iron phosphate powder;

[0070] Step 4: Disperse the low-carbon lithium iron phosphate powder and glucose obtained in step 3 in anhydrous ethanol to obtain a mixed slurry, the mass ratio of anhydrous ethanol to low-carbon lithium iron phosphate powder is 1:1, and the amount of glucose added is 6% of the mass of the low-carbon lithium iron phosphate powder. The mixed slurry is placed in a planetary ball mill for ball milling, the ball milling time is 6 hours, the ball milling speed is 800r / min, and then the ball-milled slurry is spray-dried using a spray dryer, the spray dryer has an air inlet temperature of 300°C, an air outlet temperature of 110°C, and an atomization frequency of 45Hz to obtain a carbon-coated low-carbon lithium iron phosphate precursor;

[0071] Step 5: The carbon-coated low-carbon lithium iron phosphate precursor obtained in step 4 is calcined at 700° C. for 2 h in a nitrogen atmosphere to obtain low-carbon battery-grade lithium iron phosphate.

[0072] The material discharged from step 5 is conventionally crushed and packaged to obtain a battery-grade lithium iron phosphate product with a carbon content of 1.01% and a discharge specific capacity of 143 mAh / g at 1C.

[0073] Example 3

[0074] Step 1: The disassembled lithium iron phosphate positive electrode sheet is calcined in a helium atmosphere at a temperature of 600° C. for 120 minutes, the calcined waste lithium carbonate powder is washed with water, and then dried at 95° C. for 12 hours to obtain waste lithium iron phosphate powder;

[0075] Step 2: Add iron oxalate and lithium phosphate to the waste lithium iron phosphate powder obtained in step 1, wherein the iron oxalate added is 40% of the mass of the waste lithium iron phosphate powder, and lithium phosphate is used as the lithium source and phosphorus source. The molar ratio of Li:Fe:P in the added lithium source, iron source, and phosphorus source is controlled to be 1.05:1.00:1.00 and dispersed in anhydrous ethanol (the mass ratio of anhydrous ethanol to the waste lithium iron phosphate powder is 1:1). The dispersed slurry is placed in a planetary ball mill and ball-milled at a speed of 1000 rpm for 10 hours. The ball-milled slurry is then spray-dried using a spray dryer. The spray dryer has an air inlet temperature of 350°C, an air outlet temperature of 105°C, and an atomization frequency of 50 Hz to obtain a low-carbon lithium iron phosphate precursor.

[0076] Step 3: The low-carbon lithium iron phosphate precursor obtained in step 2 is first kept at 450° C. for 2 hours and then kept at 800° C. for 10 hours in a helium atmosphere, and then washed and dried to obtain low-carbon lithium iron phosphate powder;

[0077] Step 4: Disperse the low-carbon lithium iron phosphate powder and glucose obtained in step 3 in anhydrous ethanol to obtain a mixed slurry, wherein the mass ratio of anhydrous ethanol to low-carbon lithium iron phosphate powder is 1:1, and the amount of glucose added is 7% of the mass of the low-carbon lithium iron phosphate powder. The dispersed slurry is placed in a planetary ball mill for ball milling. The ball milling time is 10 hours and the ball milling speed is 900 r / min. The ball-milled slurry is then spray-dried using a spray dryer. The spray dryer has an air inlet temperature of 350°C, an air outlet temperature of 105°C, and an atomization frequency of 50 Hz to obtain a carbon-coated low-carbon lithium iron phosphate precursor.

[0078] Step 5: The carbon-coated low-carbon lithium iron phosphate precursor obtained in step 4 is subjected to high-temperature calcination treatment in a helium atmosphere at a calcination temperature of 680° C. for a calcination time of 3 h to obtain low-carbon battery-grade lithium iron phosphate.

[0079] The material discharged from step 5 is conventionally crushed and packaged to obtain a battery-grade lithium iron phosphate product with a carbon content of 1.05% and a discharge specific capacity of 140 mAh / g at 1C.

[0080] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

[0081] Figure 1 The XRD diagram of the low-carbon battery-grade lithium iron phosphate prepared in Example 1 of the present invention is shown in FIG. Figure 1 It can be seen that the repaired powder has no other impurities.

[0082] Figure 2This is the electrochemical performance diagram of the low-carbon battery-grade lithium iron phosphate prepared in Example 2 of the present invention, and the test standard is GB / T42161-2022. Figure 2 It can be seen that the repaired material exhibits better discharge specific capacity at different rates.

[0083] Figure 3 a in the figure is a microscopic morphology of the lithium iron phosphate positive electrode sheet before repair in Example 3 of the present invention; Figure 3 b is a microscopic morphology of low-carbon battery-grade lithium iron phosphate prepared in Example 3 of the present invention. Figure 3 From a, we can see that the material particles before repair are obviously agglomerated and the particle size distribution is uneven. Figure 3 It can be seen from b that the particle size distribution of the repaired material is uniform and the agglomeration phenomenon is significantly improved.

[0084] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for recovering and repairing waste lithium iron phosphate powder, characterized in that: The following steps are involved: 1) calcining waste lithium iron phosphate under a protective atmosphere to obtain waste lithium iron phosphate powder; 2) mixing waste lithium iron phosphate powder, an iron source, a lithium source, a phosphorus source and an alcohol, and grinding and drying them in sequence to obtain a low-carbon lithium iron phosphate precursor; 3) calcining the low-carbon lithium iron phosphate precursor under a protective atmosphere to obtain low-carbon lithium iron phosphate powder; 4) mixing low-carbon lithium iron phosphate powder, a carbon source and ethanol, grinding, drying and calcining in sequence to obtain low-carbon battery-grade lithium iron phosphate; The waste lithium iron phosphate includes one or more of retired lithium iron phosphate positive electrode materials, unqualified slurry in the production process of lithium iron phosphate batteries, and unfilled defective products in the production process.

2. A method for recovering and repairing waste lithium iron phosphate powder according to claim 1, characterized in that: The calcination temperature in step 1) is 400-600° C. and the calcination time is 0.1-2 h.

3. A method for recovering and repairing waste lithium iron phosphate powder according to claim 2, characterized in that: The amount of the iron source added in step 2) is 10-60% of the mass of the waste lithium iron phosphate powder; The molar ratio of Li, Fe and P elements in the lithium source, iron source and phosphorus source is 1.01-1.05:1:1.00-1.03; The grinding speed is 500-1000 r / min, and the grinding time is 1-12 h.

4. A method for recovering and repairing waste lithium iron phosphate powder according to claim 3, characterized in that: The iron source in step 2) is ferric phosphate and / or ferric oxalate; The lithium source is one or more of lithium phosphate, lithium oxalate and lithium carbonate; The phosphorus source is one or more of lithium phosphate, iron phosphate and phosphoric acid.

5. A method for recovering and repairing waste lithium iron phosphate powder according to claim 4, characterized in that: The calcination in step 3) is firstly carried out at 300-500°C for 2-12 hours, and then at 600-800°C for 2-12 hours.

6. A method for recovering and repairing waste lithium iron phosphate powder according to any one of claims 1 to 5, characterized in that: The amount of the carbon source added in step 4) is 1-10% of the mass of the low-carbon lithium iron phosphate powder.

7. A method for recovering and repairing waste lithium iron phosphate powder according to claim 6, characterized in that: The carbon source in step 4) is one or more of glucose, sucrose, starch, acetylene black and carbon nanotubes.

8. The method for recovering and repairing waste lithium iron phosphate powder according to claim 7, characterized in that: The grinding speed in step 4) is 500-1000 r / min, and the grinding time is 1-12 h.

9. A method for recovering and repairing waste lithium iron phosphate powder according to claim 8, characterized in that: The calcination temperature in step 4) is 500-700° C. and the calcination time is 1-4 hours.